2016
DOI: 10.1021/acsami.6b05825
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Three-Dimensional Co-Delivery of Yamanaka Factors for Cell Reprogramming

Abstract: Reprogramming somatic cells into a pluripotent state has been widely investigated in two-dimensional (2D) systems but not described in the more biologically faithful three-dimensional (3D) scaffolds. Here, we devise a 3D porous tissue engineering scaffold that could achieve successful and efficient induction of pluripotency. To construct this 3D scaffold, nonviral hybrid nanoparticles were fabricated beforehand by employing calcium phosphate and cationized Pleurotus eryngii polysaccharide to codeliver plasmids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…In a recent study, PEG hydrogel decorated with ECM peptides including adhesion peptide RGDSP was demonstrated to be a better mimic of 3D microenvironment to maintain higher pluripotency and reprogramming efficiency of iPSCs . Although it was interesting to note that the PEG hydrogel without the enrichment peptides led to comparable reprogramming of cells as that of 3D Matrigel or on a 3D collagen scaffold . User‐defined control in synthesis of such designer sECMs rely on “click” chemistries that form orthogonal mesh‐like polymeric architecture, thus the functional cues incorporated are also orthogonally arranged, unlike uniquely sequestered cues within the ECM macromolecule in tissues.…”
Section: Moving From 3d Cell‐entrapment Devices To Cell‐modulation Plmentioning
confidence: 99%
“…In a recent study, PEG hydrogel decorated with ECM peptides including adhesion peptide RGDSP was demonstrated to be a better mimic of 3D microenvironment to maintain higher pluripotency and reprogramming efficiency of iPSCs . Although it was interesting to note that the PEG hydrogel without the enrichment peptides led to comparable reprogramming of cells as that of 3D Matrigel or on a 3D collagen scaffold . User‐defined control in synthesis of such designer sECMs rely on “click” chemistries that form orthogonal mesh‐like polymeric architecture, thus the functional cues incorporated are also orthogonally arranged, unlike uniquely sequestered cues within the ECM macromolecule in tissues.…”
Section: Moving From 3d Cell‐entrapment Devices To Cell‐modulation Plmentioning
confidence: 99%
“…Interestingly, the hiPSC reprogramming can be accelerated upon incorporating calcium-phosphate-based hybrid nanoparticles into 3D collagen scaffolds, benefiting from the controlled release of OSKM genes and the biophysical regulation of the 3D niche. 193 Additionally, gold nanoparticles have emerged as another promising platform for gene and drug delivery due to their high surface area, inertness, and easy fabrication. 194 Cationic gold nanoparticles (AuNPs) are efficient carriers because they can interact with nucleic acids as well as the negatively charged plasma membrane.…”
Section: Delivery Systems For Cell Reprogrammingmentioning
confidence: 99%
“…The delivered nucleic acids formed ionic complexes with cationic calcium ions through their electrostatic interactions, which were easily transported into cells via ion-channel-mediated endocytosis. Interestingly, the hiPSC reprogramming can be accelerated upon incorporating calcium-phosphate-based hybrid nanoparticles into 3D collagen scaffolds, benefiting from the controlled release of OSKM genes and the biophysical regulation of the 3D niche . Additionally, gold nanoparticles have emerged as another promising platform for gene and drug delivery due to their high surface area, inertness, and easy fabrication .…”
Section: Delivery Systems For Cell Reprogrammingmentioning
confidence: 99%
“…Injectable hydrogels show great promise in controlled delivery of therapeutics, cell delivery, tissue culture, and wound healing process. Crucial requirements for a successful injectable hydrogel system are (i) low viscosity of precursor solution for facile injection and low heat generation during hydrogel formation, (ii) rapid gelation under the physiological condition to minimize the release of encapsulated guest molecules and spreading of solution, (iii) degradability to facilitate transport of nutrients, and (iv) cytocompatibility of hydrogels and the species formed by the biodegradation of the hydrogels. , Required properties of an injectable hydrogel should be manipulated on the basis of type of application. For example, mechanical property of an injectable hydrogel should be higher than that of a tissue to be cultured. ,, For drug delivery application, the prepolymer should be able to load hydrophilic and hydrophobic drugs, and the hydrogel should be able to release the molecules in a sustained manner.…”
Section: Introductionmentioning
confidence: 99%